Evaluation of the role of HLA-DR antigens in Japanese type 1 autoimmune hepatitis. Issue 1 (December 2015) - Furumoto, Yohei; Asano, Toru; Sugita, Tomonori; Abe, Hiroshi; Chuganji, Yoshimichi; Fujiki, Kazuhiko; Sakata, Akihiko; Aizawa, Yoshio
Abstract Background The role of HLA-DR antigens in the clinicopathological features of autoimmune hepatitis (AIH) is not clearly understood. We examined the implications of HLA-DR antigens in Japanese AIH, including the effect of HLA-DR4 on the age and pattern of AIH onset, clinicopathological features, and treatment efficacy. Methods A total of 132 AIH patients consecutively diagnosed and treated in 2000–2014 at 2 major hepatology centers of eastern Tokyo district were the subjects of this study. The frequency of HLA-DR phenotypes was compared with that in the healthy Japanese population. AIH patients were divided into HLA-DR4–positive or HLA-DR4–negative groups and further sub-classified into elderly and young-to-middle-aged groups, and differences in clinical and histological features were examined. Clinical features associated with the response to immunosuppressive therapy were also determined. Results The frequency of the HLA-DR4 phenotype was significantly higher in AIH than in control subjects (59.7 % vs. 41.8 %, P  < 0.001), and the relative risk was 2.14 (95 % CI; 1.51–3.04). HLA-DR4–positive AIH patients were younger than HLA-DR4–negative patients (P  = 0.034). Serum IgG and IgM levels were higher (P  < 0.001 andP  = 0.007, respectively) in HLA-DR4–positive patients. These differences were more prominent in elderly AIH patients. However, there was no difference in IgG and IgM levels between HLA-DR4–positive and HLA-DR4–negative patients of the young-to-middle-aged group. There were no differences in the histological features. In patients with refractory to immunosuppressive therapy, higher total bilirubin, longer prothrombin time, lower serum albumin, and lower platelet count were found. Imaging revealed splenomegaly to be more frequent in refractory patients than in non-refractory patients (60.0 % vs. 30.8 %, P  = 0.038). HLA-DR phenotype distribution was similar regardless of response to immunosuppressive therapy. Conclusions HLA-DR4 was the only DR antigen significantly associated with Japanese AIH. The clinical features of HLA-DR4–positive AIH differed between elderly patients and young-to-middle-aged patients. Treatment response depended on the severity of liver dysfunction but not on HLA-DR antigens.